Fumonisin B1 and zearalenone contamination of wheat in Croatia and influence of fungicide treatments - Ivic, Dario; Domijan, Ana-Marija; Peraica, Maja; Cvjetkovic, Bogdan (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ), 2009)
In Croatia, a trial was conducted to determine the presence of the Fusarium mycotoxins fumonisin B1 and zearalenone in wheat kernels and to evaluate the efficacy of nine fungicides on Fusarium head blight severity as well as fumonisin B1 and zearalenone accumulation in wheat grain. Fumonisin B1 and zearalenone were detected in all grain samples in mean concentrations ranging from 182.0 to 446.6 µg kg-1 (fumonisin B1) and from 2.59 to 5.33 µg kg-1 (zearalenone). No significant differences were found among fumonisin B1 and zearalenone content in wheat grain for the different fungicide treatments. No correlation was revealed between Fusarium head blight severity and fumonisin B1 or zearalenone content in wheat grain, nor between fungicide efficacy and fumonisin B1 or zearalenone content in wheat grain. Under conditions of high disease pressure, efficacy of the fungicides was between 85.7% (tebuconazole + triadimefon) and 72.1% (carbendazim).